41.6k views
5 votes
Please answer question now

Please answer question now-example-1
User ICrus
by
4.9k points

1 Answer

3 votes

Answer:

3

Explanation:

2 tangents of a circle drawn from an external point are said to be congruent, according to the two-tangents theorem. Thus:

MN = ML (both tangents from external point M)

ML = 6 - KL

KL = KJ (tangents from point K)

PQ = QJ = 1 (tangents from point Q)

Therefore, KJ = 4 - 1 = 3

Since kJ = KL = 3,

ML = 6 - KL = 6 - 3

ML = MN = 3

User Rahul Katariya
by
4.6k points